Sexual orientation and physical activity for men - Lightner, Joseph Scott (Kansas State University, 2016)
Engagement in regular physical activity is essential to prevent chronic diseases, yet few individuals are active enough to receive health benefits. Social factors such as relationship status, social support, and social capital are important for engagement in physical activity, although research investigating this area has not accounted for sexual orientation, including gay and bisexual men. The purpose of this dissertation was to examine the associations between relationship status, social support, and social capital by sexual orientation for men by using national-level epidemiologic data from the National Institutes of Health. Chapter one reviewed the literature examining the relationship among social variables, physical activity and sexual orientation to identify the gaps in sexual orientation/physical activity research. Chapter two used logistic regression to identify the prevalence of meeting physical activity recommendations for single and coupled gay and straight men by determining the association between relationship status and physical activity by sexual orientation. Coupled gay men were 1.61 (95% CI: 1.01-2.56) times more likely to meet physical activity recommendations compared to coupled straight men. Chapter three used linear and logistic regression to test the relationships between social support and physical activity by sexual orientation. Social support was not related to increases in physical activity for gay (AOR: 0.98, 95% CI: 0.49-1.97) or bisexual (AOR: 0.64, 95% CI: 0.28-1.51) men as it was for straight men (AOR: 1.63, 95% CI: 1.44-1.90). Chapter four used multiple group structural equation modeling to test the association between social capital and physical activity by sexual orientation. Social capital was related to more light/moderate-intensity physical activity for gay (β = .14, p <.05) and straight men (β = .06, p <.001), and social capital was related to more vigorous-intensity physical activity for straight men only (β = .06, p <.001). Lastly, chapter 5 introduces a conceptual model of how sexual orientation is related to social variables, and ultimately, physical activity. These results provide insight into the complex associations among a social determinant of health and physical activity while highlighting the need for future descriptive and intervention studies.
Keywords: Epidemiology; Public health; LGBTQ studies